PENGARUH PENGGUNAAN VIRTUAL PHYSICS LABORATORY TERHADAP PENGUASAAN KONSEP DAN KETERAMPILAN PROSES SAINS DI KELAS XII SMA - Eka Ratnasari (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2023)
This study aims to determine the effect of the Virtual Physics Laboratory (ViPhyLab) on the mastery of the concepts and skills of physics science processes at SMA N 4 Tanjung Jabung Barat. Students' mastery of concepts at SMA N 4 Tanjung Jabung Barat is still low, indicating low science process skills. This is due to the not optimal use of ICT-based learning media and inadequate facilities and infrastructure. This type of Â research isÂ quasy experiment with this research sample using total sampling consisting of 2 classes as the experimental class and the control class. The instruments used in this study were multiple choice questions to measure mastery of concepts and essay questions and non-tests (observation sheets) to measure science process skills. The correlation coefficient value for concept mastery and science process skills is 0.993, a very strong category with a significant (2-tailed) < 0.001. The MANOVA test results obtained a significant level of 0.000 a (0.05). So that Ho is rejected and H1 is accepted. So it can be concluded that there is a significant influence of the Virtual Physics Laboratory learning media on the mastery of concepts and science process skills in class XII IPA 1 SMA N 4 Tanjung Jabung Barat.